Produção de alface e rabanete, sob adubação orgânica em ambiente protegido - Oliveira Filho, Luís Carlos Luñes de (2009)
This study was carried out with the objective to evaluate the agronomic performance of lettuce under organic fertilization, as first culture, and of radish, as second culture, as a function of the residual effect of the organic fertilization to lettuce in protected environment. It were used vases filled with 6Kg of fine land dried to the air of a soil classified as a Albaqualf (Planossolo Háplico), cultivated with lettuce, Itapuã 401 cultivar, and soon after with radish, Crimson Gigante cultivar. The calculation of fertilization and liming was carried out based on the nitrogen need of the culture of lettuce, according to the recommendations of the Commission of Chemistry and Fertility of the Soil of the RS/SC. The fertilization for the culture of radish was the residual one of the fertilization for the culture of lettuce. The used treatments consisted of mineral fertilization, vermicompost of bovine manure and liming, being: T1 Mineral seasoning + lime (recommended dose); T2 Vermicompost of bovine manure (recommended dose); T3 Vermicompost of bovine manure (1½ of the recommended dose); T4 Vermicompost of bovine manure (recommended dose) + lime; T5 Vermicompost of bovine manure (1½ of the recommended dose) + lime. The effects of the treatments on the production and nutrition of lettuce and radish and on the fertility of the soil after the harvests were evaluated. Considering the obtained results and the conditions under which the present work was carried out, it is concluded that: the application of vermicompost of bovine manure raises and maintains pH(water); the production of lettuce is increased with liming and application to the soil of vermicompost of bovine manure; the lettuce responded adequately to the fertilization meeting the nutritional needs of the culture in both the harvests; the residual effect of the fertilization with vermicompost of bovine manure and mineral fertilization provided a satisfactory production and answered for the nutritional needs of the radish; the quality of the produced roots was not affected in the treatments with vermicomposts, with or without lime application and the treatment with mineral fertilization presented low percentage of cracked and spongeous roots.